EFEKTIFITAS MODEL PEMBELAJARAN DIRECT INSTRUCTION UNTUK MENINGKATKAN HASIL IPA PADA SISWA KELAS VII SMPN 2 CIKARANG BARAT KABUPATEN BEKASI MELALUI METODE DISKUSI DI SEMESTER 1 TAHUN 2018/2019 - PRIYANTO, EDI (Pedagogiana : Jurnal Pendidikan Dasar, 2021)
The aim to be achieved in this research is to find out the extent to which the improvement of science learning outcomes for science object material and its measurement by applying the direct instruction learning model through the discussion method. The source of the data for this research is the seventh grade students of SMPN 2 Cikarang Barat, Bekasi Regency, with a total of 26 students. This research was carried out in semester 1 of the 2018/2019 academic year for 4 months. The data collected is quantitative and qualitative data. Quantitative data is data obtained from formative test results in each cycle. While qualitative data in the form of observations in each learning cycle. The data obtained is then converted to the success criteria to determine whether student learning outcomes can be seen how the improvement. The results of the study on the application of direct instruction learning models through discussion methods to improve science learning outcomes for science object materials and their measurements, in the pre-cycle 58.27 with 11 completed from 26 students, increased in the first cycle of meeting 1 which was 63.27 with 12 students who completed, in the first cycle of meeting 2, namely 68.27 with 13 students who completed, then in the second cycle of meeting 1 it increased again, namely 74.81 with 16 students who completed from 26 students, in the second cycle of meeting 2 it increased again, namely 87.50 with 24 students who finished from 26 students of class VII SMPN 2 Cikarang Barat Bekasi Regency. While the percentage of completeness also increased from pre-cycle 42.31%, increased in the first cycle of the first meeting of 46.15%, in the first cycle of the second meeting of 50%, increased to 61.54% in the second cycle of meeting 1 and increased again to 92 ,31% in the second cycle of meeting 2. From the research data, it was found that there was an increase in learning outcomes of science learning materials for science objects and their measurements in class VII students of SMPN 2 Cikarang Barat, Bekasi Regency after the application of the direct instruction learning model through the discussion method so that it was feasible to be applied in SMPN 2 Cikarang Barat Bekasi Regency.